2019
DOI: 10.1111/are.14199
|View full text |Cite
|
Sign up to set email alerts
|

First step of non‐fish meal, non‐fish oil diet development for red seabream, (Pagrus major), with plant protein sources and microalgaeSchizochytriumsp

Abstract: Fish meal and fish oil are considered as the most nutritious and digestible ingredients for marine fish. The prices of both ingredients are higher than the other protein and lipid sources, such as soybean meal and corn gluten meal, and those have made downward trend of usage amount of fish meal and fish oil in aquaculture. The demand of those two ingredients has shown unbalanced conditions for the decades. According to the FAO, the disparity of supply and demand will continue to increase with the continuous wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…rivoliana (Kissinger et al, 2016), P . major (Seong et al, 2019) and P . olivaceus (Qiao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…rivoliana (Kissinger et al, 2016), P . major (Seong et al, 2019) and P . olivaceus (Qiao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The same results have been obtained with the use of S. limacinum in diets for S. salar (Kousoulaki et al, ,2015(Kousoulaki et al, , , 2020, . lanceolatus (Garcia-Ortega et al, 2016), S. rivoliana (Kissinger et al, 2016), P. major (Seong et al, 2019) and P. olivaceus (Qiao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, some studies suggest that the global warming could affect the production of DHA and consequently its availability for human consumption in the future [68]. Colombo et al [69] studied different scenarios for DHA availability in the next 100 years, taking in consideration the effect of global warming on DHA production by algae. The prediction model suggested that in the worst scenario only 4% of the global population could have access to recommended DHA intake.…”
Section: Traditional Sources For Omega-3 Polyunsaturated Fatty Acid Consumptionmentioning
confidence: 99%
“…Fish meal made from waste of silver catfish (FM) tested in the feeding of juveniles, is considered as an alternative sustainable for this species (Rossato et al, 2018). Fish meal has an adequate percentage of fatty acids that is essential for early fish development (Sargent et al, 1999, Seong et al, 2019. According to Vizcaíno et al (2014) the rising costs of fish meal worldwide promote great research effort aimed to find alternative and renewable ingredients for aquafeeds.…”
Section: Introductionmentioning
confidence: 99%